A tool for selecting patients with a high probability of sustained virological response to peginterferon alfa‐2a (40kD)/ribavirin. (9th January 2014) - Ferenci, Peter; Aires, Rodrigo; Ancuta, Ioan; Arohnson, Andrew; Cheinquer, Hugo; Delic, Dragan; Gschwantler, Michael; Larrey, Dominique; Tallarico, Ludovico; Schmitz, Manuela; Tatsch, Fernando; Ouzan, Denis
Abstract Background & Aims Pretreatment identification of patients likely to achieve a sustained virological response (SVR) with peginterferon alfa‐2a/ribavirin would be useful for individualizing treatment choices. The aim of this analysis was to devise a simple scoring system to identify patients with high probability of achieving an SVR with peginterferon alfa‐2a/ribavirin. Methods Using data from 2109 Caucasian treatment‐naive hepatitis C virus (HCV) genotype 1 mono‐infected patients from the PROPHESYS cohorts, the relationship between favourable baseline characteristics and SVR was explored using generalized additive model analysis, and a scoring system was devised to predict SVR. Results Points were assigned for: age (years) (≤35: 2; >35, ≤45: 1; >45: 0); body mass index (kg/m2) (≤20: 2; >20, ≤22: 1; >22: 0); HCV RNA (IU/ml) (≤100 000: 3; >100 000–400 000: 2; >400 000–800 000: 1; >800 000: 0); platelets (>150 ×109/l: 1; ≤150 ×109/l: 0); alanine aminotransferase [×upper limit of normal (ULN)] (>3: 1; ≤3: 0); serum aspartate aminotransferase (×ULN) (≤1: 1; >1: 0). 1029, 698 and 382 patients had scores of 0–2, 3–4 and ≥5, respectively, among whom SVR rates were 35.0, 54.9 and 76.7%. SVR in patients with scores ≥5 and undetectable HCV RNA by week 4 was 86.7%. The score was tested against two databases of patients who received peginterferon alfa‐2a/ribavirin in other clinical trials; similar high SVR rates in patients with scores ≥5 were reported. Conclusions The scoring system can reliably identify treatment‐naive HCV genotype 1 mono‐infected Caucasian patients who have a high probability of achieving an SVR with peginterferon alfa‐2a/ribavirin and will be particularly useful where protease inhibitors are not readily available.